Mining software development process variations - Santos, R. (2015)
Process tailoring aims to customize a software process to better suit the specific needs of an organization when executing a software project or due to a social context in which the process is inserted. Tailoring happens, in general, through variations in the process elements, such as activities, artifacts, and control flows. This paper aims to introduce a technique that uses process mining to uncover elements from the software process that are candidates for tailoring. The proposed approach analyzes the execution logs from several process instances that share a common standard process. As a result, execution traces that differ from the standard process flow are identified and assessed to uncover their variable elements. The proposed technique was evaluated with data extracted from a real software development scenario when a large system was under development for a set of Brazilian Federal Institutes of Education, Science and Technology.